Cloud Elasticity for HPC Applications: Observing Energy, Performance and Cost - Facco Rodrigues, Vinicius; Rostirolla, Gustavo; da Rosa Righi, Rodrigo; Andre da Costa, Cristiano; Victória Barbosa, Jorge Luís (2015)
Elasticity is one of the most known capabilities related to cloud computing, being largely deployed using thresholds. In this way, limits are used to drive resource mangement actions, leading to the following problem statements: How can cloud users set the threshold values to enable elasticity in their cloud applications? And what is the impact of the application's load pattern in the elasticity? This article answers these questions for iterative high performance computing applications, showing the impact of both thresholds and load patterns on application performance and resource consumption. To accomplish this, we developed a reactive and PaaS-based elasticity model called AutoElastic and employed it over a private cloud to execute a numerical integration application. Here, we are presenting an analysis of best practices and possible optimizations regarding the elasticity and HPC pair. Considering the results, we observed that the upper threshold influences the application time more than the lower one.
Keywords: Cloud elasticity; high-performance computing; resource; management; self-organizing